Sosialisasi Penyusunan Laporan Keuangan Menggunakan Microsoft Excel (Streetsteamgruop) - Maulana, Sidik; Gayatri, Ida Ayu Made Ermeytha; Irwanto, Tito; Wagini, Wagini (Jurnal Gotong Royong, 2024)
This activity aims to socialize the use of Microsoft Excel as a tool for preparing financial reports for small businesses, especially streetstemgroup. Small businesses often face challenges in managing their finances effectively, which can impact business sustainability and growth. Good preparation is essential for monitoring cash flow, identifying profitability, and meeting tax obligations. However, many small business owners do not have the knowledge or resources to implement complex financial reporting systems. In this outreach, we developed a training module that teaches the basics of preparing financial reports using Excel. This module covers how to record daily transactions, create a general journal, post to a general ledger, prepare a trial balance, and produce financial reports such as a balance sheet, profit and loss report, and cash flow report. This training was carried out in several sessions with a practical approach, where participants directly practiced financial recording and analysis using Excel. With better bookkeeping, it is hoped that small businesses can optimize their financial performance, make better business decisions, and increase their ability to survive and thrive in a competitive market. Recommendations for further activities include further module development and providing ongoing support for small businesses in implementing technology-based financial bookkeeping.